2012
DOI: 10.1148/radiol.12111700
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Dual-Phase Whole-Heart MR Imaging: Clinical Implications for Congenital Heart Disease

Abstract: Certain structures in CHD are better imaged in systole and others in diastole, and therefore, the dual-phase approach allows a higher overall success rate. This approach also allows depiction of diameter changes between systole and diastole and is therefore preferable to standard single-phase sequences for the planning of interventional procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…In a previous report on the use of navigator-gated 3D whole heart acquisition in CHD patients, Sørensen et al [ 16 ] reported that 21 out of 52 datasets (40 %) were excluded because of an inadequate image quality. In a pediatric population, Hussain et al [ 27 ] described the performance of a dual-phase, i.e. systolic and diastolic navigator-gated 3D acquisition for the assessment of the great vessels including the caval veins and the pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report on the use of navigator-gated 3D whole heart acquisition in CHD patients, Sørensen et al [ 16 ] reported that 21 out of 52 datasets (40 %) were excluded because of an inadequate image quality. In a pediatric population, Hussain et al [ 27 ] described the performance of a dual-phase, i.e. systolic and diastolic navigator-gated 3D acquisition for the assessment of the great vessels including the caval veins and the pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%
“…However new dual-phase b-SSFP sequence could be used in order to evaluate the intracardiac anatomy in both systole and diastole. 9 Other imaging alternatives could be magnetic resonance contrast-enhanced or computed tomography. We acknowledge that, although this segmentation algorithm is not a limitation in the reproduction of the vessel wall, it does not truly represent the myocardial wall thickness but the ventricular cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiogram-gated three dimensional of the whole heart is a useful MRI sequence to assess the great vessels, the coronary arteries, and the cardiac chambers in patients with complex CHD including hypoplastic left heart syndrome. 4,5,14 In this study, a combination of short-axis cine and three-dimensional whole heart demonstrated the anatomy of papillary muscles in all patients. These sequences are already a part of the MRI protocol in our centre in the assessment of patients with hypoplastic left heart syndrome before undergoing surgery and during follow-up.…”
Section: Discussionmentioning
confidence: 54%